(untitled) (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Public financial management is a vital element in realizing transparent, accountable, and service-oriented governance. However, the complexity of the planning, budgeting, implementation, and accountability processes at the regional level often gives rise to various risks that can hamper the effectiveness of government administration. This study aims to analyze risk control strategies in public financial management in North Sumatra Province, identify the most dominant types of risks, and evaluate the effectiveness of control mechanisms implemented by the regional government. The research method uses a qualitative approach with data collection techniques through documentation studies, interviews with regional financial management officials, and analysis of financial reports and supervisory findings. Data analysis was conducted descriptively with reference to the enterprise risk management (ERM) framework and the Government Internal Control System (SPIP). The results show that the main risks in public financial management in North Sumatra include the risk of inaccurate planning, budget implementation discrepancies, administration and procurement risks, and the risk of low compliance with standard procedures. Although the regional government has implemented a number of control measures, such as increasing the role of APIP, strengthening SPIP, and utilizing information technology, their effectiveness remains limited due to variations in human resource capacity, suboptimal crossunit coordination, and a weak risk management culture. This study concludes that risk control strategies in North Sumatra need to be directed at strengthening data-based risk identification, integrating oversight with planning and budgeting processes, improving staff competency, and implementing an integrated information system that supports sustainable control. The findings of this study are expected to serve as a reference in developing more comprehensive risk management policies in the public sector, particularly in improving the accountability and effectiveness of regional budget management